2000
DOI: 10.1524/zpch.2000.214.1.129
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Carbon Particle Formation and Decay in Carbon Suboxide Pyrolysis behind Shock Waves

Abstract: The formation of carbon particles following the pyrolysis of C

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…However, this behavior of the process is realized until the reverse reactions of the decomposition of clusters and nanoparticles come into play due to an increase in temperature. It was shown in [9,10] that as the temperature behind the shock wave increases to 2800-3000 K, the rate of particle formation slows down. At T = 3000 K, the total time of particle growth is more than 100 μs, and at T = 3400 K the rate of the decay (evaporation) of the particles is higher than the rate of their formation [10].…”
Section: Analysis Of the Obtained Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, this behavior of the process is realized until the reverse reactions of the decomposition of clusters and nanoparticles come into play due to an increase in temperature. It was shown in [9,10] that as the temperature behind the shock wave increases to 2800-3000 K, the rate of particle formation slows down. At T = 3000 K, the total time of particle growth is more than 100 μs, and at T = 3400 K the rate of the decay (evaporation) of the particles is higher than the rate of their formation [10].…”
Section: Analysis Of the Obtained Resultsmentioning
confidence: 99%
“…It was shown in [9,10] that as the temperature behind the shock wave increases to 2800-3000 K, the rate of particle formation slows down. At T = 3000 K, the total time of particle growth is more than 100 μs, and at T = 3400 K the rate of the decay (evaporation) of the particles is higher than the rate of their formation [10]. Consequently, it is obvious that, in contrast to the classical detonation, supported by combustion pro-cesses, this phenomenon should have an extremum in temperature, depending on the integral heat release, and the process should become self-decaying upon excessive overheating.…”
Section: Analysis Of the Obtained Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The measured particle yield did not depend on the C 3 O 2 mole fraction and had a maximum at approximately 1600 K for all mixtures. Recently, a series of measurements have been carried out to study the particle formation at a higher temperature range (from 2000 K to 3700 K) [6][7][8][9]. It was found that at the measured time of 1 ms after the reflected shock wave, the temperature dependence of the particle yield showed double bell-shaped curves with two local maxima at 1600 K and 3200 K. More recently, two studies [10,11] provided new explanations for the double bell-shaped optical densities measured in the previous experiments.…”
Section: Introductionmentioning
confidence: 99%